Nitrification Activity of the Sponge Chondrosia reniformis Under Elevated Concentrations of Ammonium - Nemoy, Philip; Spanier, Ehud; Angel, Dror L. (Frontiers in Marine Science, 2021)
This study examined the ability of a Mediterranean demosponge Chondrosia reniformis to oxidize exogenous ammonium, simulating N-rich conditions that occur near finfish farms. We hypothesized that as the concentration of ammonium increases in the surrounding seawater, nitrification mediated by microbes associated with C. reniformis will lead to enhancement of ammonium uptake, nitrate excretion and oxygen consumption by the sponge holobiont. To test this hypothesis, we conducted laboratory experiments with C. reniformis explants exposed to ammonium enrichment (300 – 6667 nM) and to ambient seawater (45 – 1511 nM ammonium). We analyzed inhaled (IN) and exhaled (EX) water samples for dissolved oxygen, ammonium, nitrates and retention of picoplankton cells. We observed ammonium uptake in nearly half the cases and excretion of nitrate in most experimental outcomes. Yet, the consumption of ammonium and oxygen, as well as the excretion of nitrate by C. reniformis were not related to the concentration of inhaled ammonium, which suggests that the nitrification activity of sponge-associated microbes is not necessarily related to the concentration of ammonium in the surrounding seawater. Further research is required to reveal the sources of nitrate released from sponges and the fate of this nitrate in natural and manipulated ecosystems.